Possibilities of using Nordic walking training in cardiac rehabilitation - Ewelina Litwa; Anna Dobosiewicz; Gracjan Różański; Nataliia Badiuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Cardiac rehabilitation means that cardiac rehabilitation should be considered as multidirectional and comprehensive activities, considering human health in a holistic approach. Cardiac rehabilitation should be implemented as soon as possible, immediately after the end of life-threatening conditions in the course of coronary events or the direct effects of invasive treatment. Many scientific studies indicate the effectiveness of Nordic Walking training in cardiac rehabilitation. It has the benefits of increasing exercise tolerance and oxygen uptake, and improves quality of life. Patients willingly choose this type of activity and tolerate it well, moreover, it is a generally available form of activity that can be practiced anytime and anywhere. This training can be recommended to a wide group of patients both as prevention and as a form of rehabilitation.